Succession of the Microbial Community Structure and Its Correlation With Physicochemical Indicators During the Fermentation of Sauce-Flavor Baijiu Fermented Grains - Ji Liu; HongYan Zhang; Ming Hui Ma; Yu Jie Zhi; Ling Liu; Xiao Shan Zhang; Jian Hua Liu; Jun Cai Hou (Journal of Food Quality)
This study analyzed the fermented grains from different stages of fermentation at the Bei Da Cang Distillery, aiming to reveal the succession patterns of bacterial communities and their relationship with physicochemical indicators during fermentation. The results showed that starch and sugar content gradually decreased, while moisture content and acidity continuously increased. Key bacterial genera such as Acetilactobacillus jinshanensis, Lactobacillus acetotolerans, Bacillus pumilus, and Lentilactobacillus kefiri dominated different fermentation rounds, with Acetilactobacillus jinshanensis being particularly prevalent in all stages, contributing to the stability of microbial communities and flavor formation. The study also found significant correlations between bacteria and physicochemical parameters. Lactobacillus acetotolerans and Lentilactobacillus kefiri significantly promoted starch degradation; the activity of Lactobacillus acetotolerans is negatively correlated with acidity. These findings provide scientific insights for optimizing fermentation conditions to improve the flavor and quality of Baijiu.